Ariadne's thread: a methodological map for researching criminal judicial cases as a historical source - Danielle Regina Wobeto de Araújo; Gabrielle Stricker do Valle (Revista Brasileira de Direito Processual Penal)
This article aims to advise legal researchers, particularly beginners, who, having access to criminal cases as their main historical source, intend to research legal history or, more specifically, the history of criminal justice. We structure this article in three sections. The first focuses on methodological reflections on the use of this type of source, highlighting its main characteristics, potentialities, and the set of problems it allows us to address. The second part provides methodological guidance for the researcher when facing a specific case. Finally, in the third part, we put into practice the precautions and arguments discussed through the analysis of secular criminal cases of witchcraft, in XVIII century Portuguese South America, with the purpose of illustrating how to construct a cultural history of criminal justice that privileges marginalized subjects and their rights cast into invisibility. Finally, we conclude by encouraging the critical use of criminal cases, which may be of special interest to those who share a practical (sociological) or realist perspective on law.